2019
DOI: 10.1002/we.2391
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of wind turbine generator failure using two‐stage cluster‐classification methodology

Abstract: Reducing wind turbine downtime through innovations surrounding asset management has the potential to greatly influence the levelised cost of energy (LCoE) for large wind farm developments. Focusing on generator bearing failure and vibration data, this paper presents a two‐stage methodology to predict failure within 1 to 2 months of occurrence. Results are obtained by building up a database of failures and training machine learning algorithms to classify the bearing as healthy or unhealthy. This is achieved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…One classification of machine learning techniques for wind turbine condition monitoring is to divide them into supervised (classification and regression) and unsupervised (clustering) learning. An example of classification for fault detection, isolation and failure mode diagnosis on the gearbox is illustrated by Koukoura et al (2019), whereas Turnbull et al (2019) applied a combination of clustering and classification techniques to group similar operating conditions and detect generator faults. An example of regression to detect anomalies in vibration indicators can be found in Verstraeten et al (2019).…”
Section: Scada-based Condition Monitoringmentioning
confidence: 99%
“…One classification of machine learning techniques for wind turbine condition monitoring is to divide them into supervised (classification and regression) and unsupervised (clustering) learning. An example of classification for fault detection, isolation and failure mode diagnosis on the gearbox is illustrated by Koukoura et al (2019), whereas Turnbull et al (2019) applied a combination of clustering and classification techniques to group similar operating conditions and detect generator faults. An example of regression to detect anomalies in vibration indicators can be found in Verstraeten et al (2019).…”
Section: Scada-based Condition Monitoringmentioning
confidence: 99%
“…Findings showed that most models use SCADA or simulated data, with almost two-thirds of methods using classification and the rest relying on regression. Neural networks, support vector machines and decision trees are most commonly used, with more recent papers now combining techniques and data sources to optimise performance such as [12,13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature, several authors report on predictive maintenance using machine learning models [6][7][8][9][10][11], deep learning based on turbine performance curves, and condition monitoring to detect vibration anomalies from cleaning and processing vibration time windows signals for information extraction [12,13]. Moreover, image processing has been used in the analysis of rotary drives to determine their reference condition [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%